2021
DOI: 10.1111/nph.17200
|View full text |Cite
|
Sign up to set email alerts
|

ERECTA signaling regulates plant immune responses via chromatin‐mediated promotion of WRKY33 binding to target genes

Abstract: Summary The signaling pathway mediated by the receptor‐like kinase ERECTA (ER) plays important roles in plant immune responses, but the underlying mechanism is unclear. Genetic interactions between ER signaling and the chromatin remodeling complex SWR1 in the control of plant immune responses were studied. Electrophoretic mobility shift assay and yeast one‐hybrid analysis were applied to identify ER‐WRKY33 downstream components. Chromatin immunoprecipitation analyses were further investigated. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 83 publications
(106 reference statements)
0
24
0
Order By: Relevance
“…This article is protected by copyright. All rights reserved responses to biotic stress (March-Díaz et al, 2007;Berriri et al, 2016;Cai et al, 2021) through transcriptional regulation of environmentally responsive genes (ERGs).…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…This article is protected by copyright. All rights reserved responses to biotic stress (March-Díaz et al, 2007;Berriri et al, 2016;Cai et al, 2021) through transcriptional regulation of environmentally responsive genes (ERGs).…”
Section: Accepted Articlementioning
confidence: 99%
“…By contrast, H2A.Z incorporation into gene-body nucleosomes generally has a repressive effect on transcription (Coleman-Derr & Zilberman, 2012;Lei & Berger, 2020); these genes tend to be environmentally responsive, and their activation is associated with H2A.Z eviction (Cortijo et al, 2017;Dai et al, 2017;Sura et al, 2017). Hence, H2A.Z controls both abiotic stress responses (Hu & Lai, 2015;Jarillo & Piñeiro, 2015;Sura et al, 2017;Kumar, 2018) and plant immune responses to biotic stress (March-D ıaz et al, 2008;Berriri et al, 2016;Cai et al, 2021) through transcriptional regulation of environmentally responsive genes (ERGs).…”
Section: Role Of Noncoding Rnas and Nuclear Ago1mentioning
confidence: 99%
“…ERECTA signaling, in tandem with the SWR1 chromatin remodeling complex (CRC), controls the expression of the PACLOBUTRAZOL RESISTANCE 1 ( PRE1 ) family genes. This observation supports their role in the GA signaling pathway, however, neither direct interaction between ERECTA and SWR1 nor the direct influence of ERECTA signaling on chromatin structure or SWR1 activity has, as yet, been demonstrated (Cai et al, 2017; Cai et al, 2021).…”
Section: Introductionmentioning
confidence: 66%
“…It plays an important role in the production of meat and dairy products ( Wilkins & Humphreys, 2003 ), but its yield is threatened by various environmental stresses. A large number of studies have shown that WRKY TFs can regulate a variety of plant processes and responses to various biotic and abiotic stresses ( Cai et al, 2021 ; Wang et al, 2020b ; Wang et al, 2020c ; Xiang et al, 2021 ). In this study, WRKY family members were first identified from orchardgrass, and all sequences were located, classified, and analyzed according to their expression profiles, which is of great significance for molecular-assisted breeding of orchardgrass.…”
Section: Discussionmentioning
confidence: 99%